Benchmark experiments for higher-order and full-Stokes ice sheet models (ISMIP-HOM) - Pattyn, Frank; Perichon, Laura; Aschwanden, A; Breuer, Beate; De Smedt, Brigitte; Gagliardini, Olivier; Gudmundsson, G.H; Hindmarsh, Richard; Hubbard, A.; Johnson, J.V; Kleiner, Thomas; Konovalov, Y; et al. (2007)
info:eu-repo/semantics/published